Saints, infirmity, and community in the late Middle Ages - Kuuliala, Jenni, author. Link Link
1 online resource (236 pages).
Keywords: Bodily suffering and patient, Christlike attitudes towards that suffering were among the key characteristics of sainthood throughout the medieval period. Saints, Infirmity, and Community in the Late Middle Ages analyses the meanings given to putative saints' bodily infirmities in late medieval canonization hearings. How was an individual saint's bodily ailment investigated in the inquests, and how did the witnesses (re)construct the saintly candidates' ailments? What meanings were given to infirmity when providing proofs for holiness? This study depicts holy infirmity as an aspect of sanctity that is largely defined within the community, in continual dialogue with devotees, people suffering from doubt, the holy person, and the cultural patterns ascribed to saintly life. Furthermore, it analyses how the meanings given to saints' infirmities influenced and reflected society's attitudes towards bodily ailments - or dis/ability - in general.